Digitalization of the construction products’ manufacturing process as a guarantee of the finished products quality - Romanenko Elena; Kim Valeria; Sandul Alexey (E3S Web of Conferences, 2021)
The article highlights the problems associated with the quality of the information platform at the enterprise, which is the guarantor of the quality of products and structures manufactured at the enterprises of the reinforced concrete complex. The article substantiates the dependence of the finished product quality parameters on the processes’ digitalization and the increase in the enterprise efficiency through the business information processes introduction in the WEB-segment. An example is given of integrating contextual advertising into the marketing sphere of an enterprise that manufactures the products for construction purposes and the implementation of the Bitrix24 system, which can be one of the most important tools in organizing the work of an enterprise through those aspects of the company that it can cover, starting with the coordination of the employees’ work, planning, analysis and administrative control as well as the economic activities of the enterprise and ending with document flow.